2017
DOI: 10.21746/aps.2017.6.11.11
|View full text |Cite
|
Sign up to set email alerts
|

In vitro screening for enzymatic activity of Trichoderma species for biocontrol potential

Abstract: A total of seven Trichoderma species were isolated from rhizosphere soils of brinjal on potato dextrose agar medium. Based on morphological and cultural characters, the isolates were assigned to different species viz., Trichoderma viride, T. harzianum, T. virens, T. atroviride, T. koningii, T. pseudokoningii and T. reesei. Trichoderma species were screened for the production of extracellular enzymes to identify the strain with high antagonistic potential against fungal pathogens. The screening was done followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The medium was cooled and poured in sterilized petri dishes and allowed to solidify. Seven days old culture plugs of Trichoderma were inoculated and incubated at 25-28 ºC for 48 hours (Ramaraju et al, 2017).…”
Section: Screening Of Trichoderma Species For Chitinase Activitymentioning
confidence: 99%
“…The medium was cooled and poured in sterilized petri dishes and allowed to solidify. Seven days old culture plugs of Trichoderma were inoculated and incubated at 25-28 ºC for 48 hours (Ramaraju et al, 2017).…”
Section: Screening Of Trichoderma Species For Chitinase Activitymentioning
confidence: 99%
“…The current results are also supported by studies that have found that the hydrolytic enzymes (cellulase, chitinase, protease, and b-(1,3)-glucanases) produced by T. asperellum, T. harzianum, and T. longibrachiatum have a high level of antagonistic activity against F. oxysporum (Schirmböck et al, 1994;Putri et al, 2022). These enzymes play a key role in the breakdown of the pathogen's cell walls, which facilitates simple invasion and colonization by the biocontrol agents, induces a defense response and slows the spread of the pathogen while also indirectly promoting plant growth and development (Qualhato et al, 2013;Cherkupally et al, 2017). Overall, T. asperellum AU131 and T. longibrachiatum AU158 isolates appear to be the most promising biological control agents against F. xylarioides, primarily because of the synergistic effect of various mechanisms of action, including mycoparasitism, competition, production of bioactive secondary metabolites, and induction of systematic resistance (Aita et al, 2019;Mulatu et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…22 Trichoderma strains are mainly characterized by their capacity to secrete a variety of extracellular enzymes, including chitinases, glucanases, and proteases. 23,24 Secretion of chitinase, glucanase, and protease are also involved in the mycoparasitism of Trichoderma asperellum GDFS1009 towards Fusarium oxysporum f. sp. cucumerinum.…”
Section: Introductionmentioning
confidence: 99%
“…Mycoparasitism is accompanied by the secretion of cell wall‐degrading enzymes that penetrate pathogen mycelium, absorbing nutrients and ultimately leading to pathogen death 22 . Trichoderma strains are mainly characterized by their capacity to secrete a variety of extracellular enzymes, including chitinases, glucanases, and proteases 23,24 . Secretion of chitinase, glucanase, and protease are also involved in the mycoparasitism of Trichoderma asperellum GDFS1009 towards Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%